2014
DOI: 10.1093/carcin/bgu089
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of NHE1 protein expression enables glioblastoma cells to escape TMZ-mediated toxicity via increased H+extrusion, cell migration and survival

Abstract: Sodium-hydrogen exchanger isoform 1 (NHE1) plays a role in survival and migration/invasion of several cancers and is an emerging new therapeutic target. However, the role of NHE1 in glioblastoma and the interaction of NHE1 expression and function in glioblastoma cells with cytotoxic temozolomide (TMZ) therapy remain unknown. In this study, we detected high levels of NHE1 protein only in primary human glioma cells (GC), glioma xenografts and glioblastoma, but not in human neural stem cells or astrocytes. GC exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 46 publications
(53 reference statements)
7
72
0
Order By: Relevance
“…Evidence suggests that NHE1 is a significant contributor to matrix degradation through local extracellular acidification or effects on MMP expression and localization (Lin et al, 2012;Putney and Barber, 2004). Increased pH i resulting from ion transporter activity has been shown to enable cancer cell migration in oncogene-transformed mammary cells (Lauritzen et al, 2012), in patient-derived glioma cell lines (Cong et al, 2014) and in cervical cancer cell lines that do not exhibit hallmarks of metabolic adaptation (De Saedeleer et al, 2014). Furthermore, increased pH i due to higher ion transporter activity has been linked to cell invasion phenotypes (Lin et al, 2012;Grillo-Hill et al, 2015).…”
Section: Migration and Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that NHE1 is a significant contributor to matrix degradation through local extracellular acidification or effects on MMP expression and localization (Lin et al, 2012;Putney and Barber, 2004). Increased pH i resulting from ion transporter activity has been shown to enable cancer cell migration in oncogene-transformed mammary cells (Lauritzen et al, 2012), in patient-derived glioma cell lines (Cong et al, 2014) and in cervical cancer cell lines that do not exhibit hallmarks of metabolic adaptation (De Saedeleer et al, 2014). Furthermore, increased pH i due to higher ion transporter activity has been linked to cell invasion phenotypes (Lin et al, 2012;Grillo-Hill et al, 2015).…”
Section: Migration and Metastasismentioning
confidence: 99%
“…Importantly, decreasing pH i or increasing pH e inhibits cell migration (Parks and Pouyssegur, 2015;Cong et al, 2014;Frantz et al, 2008;Denker and Barber, 2002). We recently described how protonation and deprotonation regulate selective pH sensors involved in cell migration (Schönichen et al, 2013).…”
Section: Migration and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…MAP4K4 binds to and phosphorylates the C-terminus of NHE1 and causes its activation, which increases the intracellular pH in proximity of the plasma membrane [13]. NHE1 is involved in cell migration control [70][71][72] and associated with metastatic functions in cancer cells [73][74][75]. GF control of this central regulator of cortical cell functions through MAP4K4 may contribute to local remodeling of the cytoskeleton [76,77] and enable the formation of invasive membrane protrusions.…”
Section: Cell Migration and Invasionmentioning
confidence: 99%
“…The ERM family is established to be important molecules in cytoskeletal activity as they link actin to the plasma membrane proteins. ERMs are frequently identified to be highly expressed in numerous cancer types and are important mediators of cell survival signaling (10)(11)(12). Previous studies have suggested that high ezrin expression may be associated with cellular motility, therefore having a role in metastasis and invasion (13)(14)(15) in T-ALL drug resistance with ezrin, an important molecule in C-C-motif chemokine ligand 25 (CCL25)-induced T-ALL metastasis (12,16).…”
Section: Introductionmentioning
confidence: 99%